Asuhan Keperawatan Keluarga Tn. D Dengan Masalah Utama Diabetes Melitus Pada Ny. R Di Dukuh Nampan Rt 2/Rw 1 Jati, Gatak, Sukoharjo - Atmaja, Ramdani Tri; , Supratman, Ph.D (2015)
Background : Diabetes mellitus is one of the degenerative diseases that currently numbers continue to grow with increasing life expectancy of the Indonesian nation. Additionally, high confidence and family to pharmacological treatment still lack knowledge of the family is a factor that is strongly associated with increased diabetes. Goal : To know the description of family nursing care in a family with diabetes mellitus. Method : The method used is to make the process of nursing care of the complete family included assessment, intervention, implementation and evaluation of nursing. Result : after nursing care a family with three visits for 30 minutes/ meeting has resolved the problem of lack of knowledge and the risk of complications resolved partially. Conclusion : after nursing care on the Mr. D family has been understood about diabetes mellitus and also already know about the complications and how to prevent it.